Bookkeeping ALL - IN - ONE for dummies - Epstein, Lita; Tracy, John A. (Hoboken, New Jersey : John Wiley & Sons Inc., 2019)
Manage the art of bookkeeping Do you need to get up and running on bookkeeping basics and the latest tools and technology used in the field? You've come to the right place! Bookkeeping All-In-One For Dummies is your go-to guide for all things bookkeeping. Bringing you accessible information on the new technologies and programs, it cuts through confusing jargon and gives you friendly instruction you can use right away. Inside, you'll learn how to keep track of transactions, unravel up-to-date tax information, recognize your assets, and so much more. Covers all the new techniques and programs in the bookkeeping field. Shows you how to manage assets and liabilities. Explains how to track business transactions accurately with ledgers and journals, Helps you make sense of accounting and bookkeeping basics Get all the info you need to jumpstart your career as a bookkeeper!
Includes index
"5 books in one!"--Cover.
Keywords: Bookkeeping